Greenfield FDI and skill upgrading - Ronald B. Davies; Rodolphe Desbordesz (University College Dublin, UCD School of Economics, 2012)
Globalisation is one of the primary accused culprits of growing income inequality in the developed world. In particular, outbound foreign direct investment (FDI) is often associated with general skill upgrading in the home country, that is, a shift in relative labour demand from low skilled workers towards more skilled workers. Nevertheless, the empirical evidence indicates that such effects are small at best, especially in contrast to those for overall trade in intermediates (which includes both intra-firm trade and foreign outsourcing). In response, we utilise a proprietary dataset on greenfield FDI. In contrast to M&A FDI, which can represent acquisition of new technologies or elimination of competitors, greenfield FDI may be more closely linked to skill upgrading, especially when its done to take advantage of international differences in factor prices. Given that our data delineate FDI by function as well as by destination country, we are able to capture the different motives of FDI and to account for the fact that different functions in different countries may substitute for different skill levels at home. Using these data in conjunction with industry-level data on seventeen developed home countries, we find that greenfield FDI results in polarised skill upgrading, i.e. an increase in the relative share of employment and compensation of the most skilled workers to the detriment of the medium skilled workers. This impact is strongest for support services (e.g. call centres), knowledge services (e.g. R&D), and retail FDI with little indication of an impact from FDI in other functions. Our estimates suggest that the change in the high skilled compensation share explained by support services is of the same order of magnitude as what is found in other studies for trade in services. Unlike those studies, however, we find that demand for medium skilled workers falls from outbound FDI whereas that of the lowest skilled workers remains unchanged. Thus, in contrast to overall trade in services where globalisation leads to increased income inequality between the lowest skilled workers and other groups, increased outbound FDI leads to an increased gap between the most skilled and the moderately skilled workers. FDI then has parallels to the results from the labour literature estimating the non-monotonic impacts on the demand for skills of computerisation and service offshoring.
Keywords: 330; Greenfield FDI; Labour Demand; Skill Upgrading